Effect of Waste Tire Crumb Rubber on the Damping Ratio and Natural Frequency of Mortar for Masonry Wall Applications - Multilawati Nasution (Universitas Negeri Padang, 2025)
This study investigated the effect of waste tire crumb rubber on the damping characteristics of mortar for masonry wall applications using the free vibration method. Beam specimens measuring 500 mm × 100 mm × 100 mm were prepared with different crumb rubber contents and two particle sizes, namely passing the No. 4 (4.75 mm) and No. 8 (2.36 mm) sieves. Free vibration tests were conducted using a cantilever beam configuration with a 15 N suspended load. The acceleration responses were recorded using a piezoelectric accelerometer connected to the Dewesoft data acquisition system and analyzed using the Fast Fourier Transform (FFT) and logarithmic decrement methods to determine the natural frequency and damping ratio. The results showed that increasing the crumb rubber content enhanced the damping ratio while reducing the natural frequency of the mortar specimens. The highest damping ratio of 4.16% was obtained for the specimen containing 60% crumb rubber passing the No. 4 sieve. These findings demonstrated that waste tire crumb rubber effectively improved vibration energy dissipation and showed considerable potential as a sustainable material for enhancing the dynamic performance of masonry mortar.